Review on a Novel Advancement in Dry Powder Inhaler - Bhagat, Pooja D.; Redasani, Vivek kumar; D. Jadhav, Prakash; Velha, Atish B.; Mahadik, Rutuja A. (Asian Journal of Pharmaceutical Research and Development, 2023)
Human health management has always been the focus area of medical practitioners across the world. Health is maintained with the right kind of food intake, regular exercise, and remedial medications whenever and wherever necessary. Medications have been an integral part of human health management and improvement ever since. Along with medications, the right kind of drug delivery mechanism plays a crucial role in the efficacy of the medications. Dry powder inhalers (DPI) are one of the most efficient and advanced targeted drug delivery mechanisms. Currently, a wide range of inhaler devices are available on the market for pulmonary drug delivery with a view to maximising drug delivery with low variability compared to other drug delivery systems. Compared to other oral, topical, and parenteral drug delivery methods, DPI’s efficiency is manifold. It has varied benefits, like rapid drug absorption due to the high density of blood vessels and the large surface area of the lungs (high lung deposition); the lungs have low enzymatic activity, so this route has a minimum risk for enzymatic degradation. Faster absorption, maximum efficiency, site target, minimum wastage, user-friendly, etc. Historically, DPIs were used only for respiratory-related ailments. But now, due to their better utility value, DPIs are also used in other maladies treatments. This research paper focuses on various advancements in the field of dry powder inhalers (DPIs), their advanced manufacturing techniques, challenges, and the evolution of technology that help maintain their versatility, stability, and reliability.